Neoadjuvant Systemic Therapy for Locally Advanced Breast Cancer in St. Luke’s Medical Center: 10-Year Local Experience and Response Rates - Mel Valerie B. Cruz-Ordinario; May Rose A. Malesido; May N. Sabando; Agnes E. Gorospe; Carlos Dy (Asian Pacific Journal of Cancer Care, 2023)
Background: Neoadjuvant therapy has given important prognostic and predictive information based on pathologic response as seen on studies showing that pathologic complete response (pCR) is associated with favorable disease-free and overall survival in some molecular subtypes. The main objective is to determine the pCR rate among patients with locally advanced breast cancer (LABC) in our institution. Method: A total of 259 patients with LABC who received neoadjuvant therapy and underwent definitive surgery at St. Luke’s Medical Center Quezon City from 2007 to 2017 were retrospectively analyzed through chart review. Results: Patients’ median age at diagnosis was 51 years old. 57% were premenopausal and 42% were postmenopausal. The most common histology was Invasive Ductal at 92%. The most common subtype was Luminal/HER2 negative (52%). Majority of the patients have Stage III disease. The most common chemotherapy regimen used was sequential Anthracycline and Taxane (AC/EC/FEC then Taxane with or without Trastuzumab and Docetaxel with or without Trastuzumab followed by FEC) at 31%, Anthracycline-based (Doxorubicin or Epirubicin with Cyclophosphamide/5FU -EC/ AC/FAC) at 28%, and concurrent Anthracycline-based and Taxane (TAC/AT/ET) at 27%. Of the 95 patients with Her 2 positive disease, 21 (22%) received anti-Her2 blockade as part of their neoadjuvant regimen. The pCR, defined as absence of invasive residual cancer in the breast and axillary lymph nodes, with or without ductal carcinoma-in-situ (DCIS) was seen in 46 patients (18%). Among the patients who achieved pCR, the most common subtype is Luminal/HER2 negative at 17% and the most common regimen used was Docetaxel followed by FEC (5FU+EC) at39%. Conclusion: Among 259 patients, pCR is achieved in 18% of patients using standard chemotherapy. This study shows that the most common neoadjuvant regimen used was sequential Anthracycline and Taxane and most common subtype is Luminal/Her negative.